Cyber security attacks to modern vehicular systems. (October 2017) - Pan, L.; Zheng, X.; Chen, H.X.; Luan, T.; Bootwala, H.; Batten, L.
Abstract: Security is a fundamental concern in modern vehicular systems. The advancement in modern vehicular systems provides many benefits such as reducing traffic congestion and improving safety and fuel economy via vehicular networks. However, many vehicular experts in industry take it for granted that Controller Area Network (CAN) bus being the most important part of a vehicle is secured and cannot be easily hacked; furthermore, cyber security experts have limited exposure to CAN bus. This paper provides in-depth explanation of CAN bus and feasible scenarios where a vehicle is no longer safe after its CAN bus is compromised. Furthermore, the inclusion of CAN bus attacking codes in a mobile malware is cost-effective for the malicious attackers but very challenging for vehicle engineers to mitigate the security risks. Based on a variety of security attacks, we analyze potential attacks and their impact on the safety of the vehicle users. A number of vulnerabilities and attack scenarios are exposed which allows malicious attackers to hamper the vehicular control systems and cause harm to the vehicle even the passengers. In this paper, we do not report on our own implementation of attacks on real vehicles; our aim is to motivate further research to improve the security of the modern vehicular systems.